Cyclodextrin nanoparticles for diagnosis and potential cancer therapy: A systematic review - Karthic, Anandakrishnan; Roy, Arpita; Lakkakula, Jaya; Alghamdi, Saad; Shakoori, Afnan; Babalghith, Ahmad O.; Emran, Talha Bin; Sharma, Rohit; Lima, Clara Mariana Gonçalves; Kim, Bonglee; Park, Moon Nyeo; Safi, Sher Zaman; et al. (Frontiers in Cell and Developmental Biology, 2022)
Cancer is still one of the world’s deadliest health concerns. As per latest statistics, lung, breast, liver, prostate, and cervical cancers are reported topmost worldwide. Although chemotherapy is most widely used methodology to treat cancer, poor pharmacokinetic parameters of anticancer drugs render them less effective. Novel nano-drug delivery systems have the caliber to improve the solubility and biocompatibility of various such chemical compounds. In this regard, cyclodextrins (CD), a group of natural nano-oligosaccharide possessing unique physicochemical characteristics has been highly exploited for drug delivery and other pharmaceutical purposes. Their cup-like structure and amphiphilic nature allows better accumulation of drugs, improved solubility, and stability, whereas CDs supramolecular chemical compatibility renders it to be highly receptive to various kinds of functionalization. Therefore combining physical, chemical, and bio-engineering approaches at nanoscale to specifically target the tumor cells can help in maximizing the tumor damage without harming non-malignant cells. Numerous combinations of CD nanocomposites were developed over the years, which employed photodynamic, photothermal therapy, chemotherapy, and hyperthermia methods, particularly targeting cancer cells. In this review, we discuss the vivid roles of cyclodextrin nanocomposites developed for the treatment and theranostics of most important cancers to highlight its clinical significance and potential as a medical tool.